Late distant recurrence of breast carcinoma and metastasis to the main bronchus and choroid: A case report. Issue 20 (May 2018) - Luo, Zhijie; Cai, Qin; Zhao, Yuanyuan; Wang, Xiaochuan; Fu, Siying; Zhai, Linzhu
Abstract: Rationale: Metastases of breast carcinoma to the main bronchus and choroid are rare, but have been reported in relevant literature. Late distant recurrence of breast carcinoma after more than 20 years is extremely rare. Herein, we report a 57-year-old woman with late distant recurrence and metastasis to the main bronchus and choroid almost 28 years after surgery. Patient concerns: At the age of 29, the patient underwent chemotherapy and endocrine treatment after a right side mastectomy to remove breast carcinoma. The patient was hospitalized for a cough with blood-tinged sputum, dysphagia, and blurred vision in the left eye at the age of 57. Diagnoses: On evaluation, laboratory findings detected the elevated serum tumor markers of CA12-5, CA15-3, NSE, and Cyfra21-1. The imaging showed left lung metastase, multiple lymph node metastases, and small suspected metastases in the both sides of parietal lobes. Fundus fluorescein angiography showed choroidal occupying lesion of the left side which indicates secondary metastasis and retinal detachment. Combined with the pathological finding via fiberoptic bronchoscopic biopsy, the patient was clinically diagnosed with a late distant recurrence of breast carcinoma. Interventions: The patient received oral endocrine therapy of letrozole, but she refused chemotherapy, radiotherapy and other topical treatments. Outcomes: At the 3-month follow-up visit, the multiple lesions of the left lung and lymph nodes had partially regressed, and the lesion of right parietal lobe had disappeared. The patient's clinical symptoms, such as blood-tinged sputum and dysphagia, had significantly improved. Lessons: We have described this case and reviewed the relevant literature concerning late distant recurrence of breast carcinoma. Importantly, this case indicates that patients with HR positive breast carcinoma are more likely to develop late distant recurrence and clinicians should not ignore the follow-up examinations even more than 20 years after the surgery.